Protecting the Rights of Mental Health Patients: Comparative Study between Indonesia and Taiwan - Wahyu, Muhammad Arizka; Elven, Tareq Muhammad Aziz (Indonesian Comparative Law Review, 2020)
The phenomenon of human shackling upon people with mental health disorder are still found in Indonesia. The latest data from Human Rights Watch shows that more than 18,800 people now live in shackled in Indonesia. The paper aims to elaborate the existing regulation on mental health patients in Indonesia and analyze necessary steps to be taken by the Indonesian Government to provide better protection for mental health patients. This normative legal research employs comparative approach. Comparison was made with Taiwan. The study shows that human shackling still persists in Indonesia due to some reasons including the inadequacy of regulations, the lack of mental health hospitals, the shortage of psychiatrists and other mental health providers, as well as the lack of educations.